Święty Mikołaj z Myry w wielkich formach muzycznych średniowiecza, renesansu i baroku. Zarys problematyki - Towarek, Piotr (Vox Patrum, 2025)
This article is an attempt at a preliminary presentation of selected great musical forms of the Middle Ages, Renaissance and Baroque periods, which are dedicated to St. Nicholas of Myra (d. 345). These are examples of mass propers, especially Alleluia chants with a verse and sequences (Congaudentes exsultemus; Sospitati dedit egros), as well as motets from the Renaissance period (Martini, Palestrina, di Lasso, Regnart, Gallus, Vaet). These works show St. Nicholas as a bishop, a believer, a guardian and a miracle worker, which is a clear reference to the lives, stories and legends we know. The third group of compositions presented in the article are Baroque oratorios (Bononcini, Veracini, Falco, Carapella, Leo). They confirm the cult and memory of St. Nicholas on the Apennine Peninsula (especially in the Kingdom of Naples), in other parts of Europe (the Habsburg state, the court of the Bishop of Olomouc) and in the piety of confraternities and brotherhoods to which the saint was patron. These non-liturgical works, performed during Lent, show the little-known image of St. Nicholas as a young man matured by the love of his parents and embarking on his education (studies). The central theme in the oratorios is the conversion (Clizio, St. Nicholas’ friend) that takes place through patient dialogue, conversation, and even a dispute with the future bishop of Myra. St. Nicholas appears here as a teacher of repentance and Christian virtues. The fact that his person, life and intercession are commemorated during the Lenten season and not during Advent (December 6) or Christmas is a special value, which is enriched by the musical works mentioned in the article.